DEVELOPMENT OF INTERACTIVE WORLD HISTORY BABON BOOK APPLICATION BASED ON BIG DATA AS A DIGITAL LEARNING SOURCE FOR HISTORY EDUCATION STUDENTS IN MBKM CURRICULUM - Abd Haris Nasution; Flores Tanjung; Rosmaida Sinaga (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This research is motivated by the need for an Interactive World History Babon Book Application as a big data-based digital learning resource that can be accessed by students of the Department of History Education from all over the country. This application is needed to answer the challenges of Education in the Industrial Revolution Era 4.0 and the Independent Learning Curriculum of the Independent Campus. In learning world history/spatial history, lecturers and students usually only use printed teaching resources whose content is not relevant to the CPL-CPMK Department of History Education FIS UNIMED. This is because the currently available baboon printed books only contain limited material about the history of human civilization with a limit of years in the 20th century, while in the 21st century there have been drastic changes in culture and civilization experienced by humans, coupled with the outbreak of a pandemic that has plagued humans. also change the pattern of human life habits. Then the use of the interactive world history baboon book application will make it easier for students of the History Education Department to explore other learning resources in the form of multimedia such as audio, video, animation, photos, graphics, etc. In addition, the application will give students access to historical archives from the KITLV, ANRI, National Library sites, to the latest scientific articles through the national.international Journal links that will be available on the application. Therefore, research on the development of the big data-based Interactive World History Babon Book Application that is connected to it is important to do. As for the formulation of the problem, among others: 1) How to develop an interactive World History Babon book application based on Big Data as a digital learning resource for History Education Students in the Merdeka Belajar Kampus Merdeka Curriculum? 2) How is the Effectiveness of the Big Data-based interactive World History Babon book application as a digit.